Some bibliometric correlates of quality in scientific research - Lawani, S.M. (1986)
The following kinds of data were collected on three samples of cancer research literature representing three levels of quality: (1) collaboration as measured by the number of authors per paper, (2) quantitative productivity of countries, (3) diachronous citations covering the first five years of publication, (4) total self-citations, (5) proportions of self-citations made by first-named authors, and (6) the extent of dispersion of articles among journals. Analyses showed that as the number of authors per paper increases, the proportion of high quality papers also increases and the Collaborative Index can be used to measure quality in the aggregate. It was found that the quantity and quality of cancer research done in a country are positively related. All analyses of the citation data confirmed the hypotheses that highly rated papers are significantly more highly cited than average papers and the rates of uncitedness decline with quality. The proportion of self-citations to total citations decreases with increasing quality and, on average, first-named authors of quality papers cite them proportionally fewer times than first-named authors of run-of-the mill papers do. This study also shows that, as quality increases, the extent of literature scatter or dispersion increases.